Islamic Fintech Opportunities and Challenges in Advancing Financial Inclusion Among Muslim Communities in Indonesia - Ayu Gumilang lestari; Layaman; Dendy Novandi (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
Indonesia, as the country with the largest Muslim population in the world, holds significant potential for the development of financial technology (fintech) based on sharia principles. However, despite the size of this population, the level of Islamic financial inclusion remains far from optimal. This article critically examines the opportunities and challenges faced by Islamic fintech in enhancing financial inclusion among Muslim communities in Indonesia. Employing a critical analytical approach grounded in scholarly literature, this study identifies key factors influencing the adoption of Islamic fintech, including financial literacy, public trust, regulatory compliance, and the depth of sharia substance embedded in digital financial products. The findings indicate that Islamic fintech has the potential to serve as a transformative instrument for expanding financial access, but this potential can only be realized if it is supported by adequate education, substantive sharia supervision, data security, and a collaborative ecosystem involving Islamic banks, pesantren, micro, small, and medium enterprises (MSMEs), and Islamic social institutions.